To stay or not to stay? A clash of arbitration and insolvency regimes - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2021)
In the wake of the global Coronavirus disease 2019 (COVID-19) pandemic, a rise in creditorinitiated winding-up proceedings is likely to be impending in coming years (See e.g., RCMA Asia Pte. Ltd. v. Sun Electric Power Pte. Ltd. [2020] SGHC 205). At the same time, geopolitical developments, such as the scale and ambition of Belt & Road Initiative projects, have raised questions over the issue of debt sustainability. Given the prevalence of arbitration clauses in modern international commercial and project agreements, the interplay and relationship between insolvency and dispute resolution, and especially arbitration, requires careful attention. While the intersections between the arbitration and insolvency regimes are numerous and multi-faceted, (Jennifer Permesly et al. ‘IBA Toolkit on Insolvency and Arbitration’ International Bar Association (March 2021), www.ibanet.org/LPD/Dispute_Resolution_Section/ Arbitration/toolkit-arbitration-insolvency.aspx (accessed 18 April 2021) the impact of an arbitration clause on winding-up petitions has attracted recent case law. The English, Hong Kong, and Singapore courts have each taken differing approaches to the question of how to deal with winding-up petitions presented over disputed debts that are subject to an arbitration clause. On one end of the spectrum, the Hong Kong courts currently appear to prefer a relatively more creditor-friendly approach. On the other hand, the Singapore Court of Appeal recently laid down a relatively more debtor-friendly approach. Undertaking a comparative analysis of the approaches taken by different common law jurisdiction, this article argues that the Singapore Court of Appeal’s approach is preferable. However, at least for courts in United Nations Commission on International Trade Law (UNCITRAL) Model Law jurisdictions (or jurisdictions where the mandatory stay regime of the Model Law is adopted), they ought to find that a disputed debt subject to an arbitration clause falls within the scope of the mandatory stay regime under the Model Law. This article further suggests a possible way in which the approach of the Singapore Court of Appeal can be reconciled with the mandatory stay regime under Singapore’s enactment of the Model Law.